2021
DOI: 10.4103/jehp.jehp_113_21
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perspective on online teaching during pandemic

Abstract: BACKGROUND: COVID-19 pandemic has forced medical education to undergo sudden metamorphosis from the traditional face-to-face education to distance online learning. This transition was dealt with a lot of infrastructure and technical difficulties from both teacher and learner ends, especially in a developing country like India. This study was conducted with the aim of analyzing students’ perspective and problems faced in the live online teaching. MATERIALS AND METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(43 reference statements)
2
5
2
Order By: Relevance
“…Like our study results, a study done by Saurabh et al, 2021 concluded that about 62.7 percent of undergraduate students had adequate internet access. (Saurabh et al, 2021) In contrast to our study results a study done by Kala et al, in 2021, in Uttarakhand found only 8 percent of the students hail from rural areas and about 13 percent resided in hilly areas. (Kala et al, 2021) This difference might be due to the rate of admission of students from rural and urban areas varying in different states of India.…”
Section: Resultscontrasting
confidence: 95%
See 4 more Smart Citations
“…Like our study results, a study done by Saurabh et al, 2021 concluded that about 62.7 percent of undergraduate students had adequate internet access. (Saurabh et al, 2021) In contrast to our study results a study done by Kala et al, in 2021, in Uttarakhand found only 8 percent of the students hail from rural areas and about 13 percent resided in hilly areas. (Kala et al, 2021) This difference might be due to the rate of admission of students from rural and urban areas varying in different states of India.…”
Section: Resultscontrasting
confidence: 95%
“…(Saurabh et al, 2021) In contrast to our study results a study done by Kala et al, in 2021, in Uttarakhand found only 8 percent of the students hail from rural areas and about 13 percent resided in hilly areas. (Kala et al, 2021) This difference might be due to the rate of admission of students from rural and urban areas varying in different states of India. In the same study, they found about 62 percent of the students had access to uninterrupted networks.…”
Section: Resultscontrasting
confidence: 94%
See 3 more Smart Citations